Simultaneous determination of atorvastatin and ezetimibe from combined pharmaceutical products by micellar electrokinetic capillary chromatography - Blanka Székely-Szentmiklósi; Gabriel Hancu; István Székely-Szentmiklósi; Béla Kovács; Hajnal Kelemen (Universidade de São Paulo, 2017)
Abstract A rapid and sensitive micellar electrokinetic capillary chromatography method with UV photodiode-array detection was developed for the simultaneous determination of atorvastatin and ezetimibe in fixed dose drug combination. Experimental conditions such as buffer concentration and pH, surfactant concentration, system temperature, applied voltage, injection parameters were optimized in order to improve the efficiency of the separation. The best results were obtained when using fused silica capillary (48 cm length X 50 µm ID) and 25 mM borate buffer electrolyte at pH 9.3 containing 25 mM SDS, + 30 kV applied voltage, 20 ºC system temperature. The separation was achieved in approximately 2 minutes, with a resolution of 7.02, the order of migration being atorvastatin followed by ezetimibe. The analytical performance of the method was verified with regard to linearity, precision, robustness and the limit of detection and quantification were calculated.